Superiority of combining psychopathology and the second-generation cognitive science: a discussion of Kristopher Nielsen’s pluralist approach - Shang, Yaming; Dong, Da; Liu, Qingming; Li, Jiali (Frontiers in Psychology, 2025)
In recent years, advancements in the second-generation cognitive science have significantly contributed to interdisciplinary progress at the intersection of psychopathology and cognitive sciences. This article critically examines Kristopher Nielsen’s 3E framework—embodied, embedded, and enactive—which challenges traditional conceptual models of mental disorders. By emphasizing the dynamic interplay among the brain, body, and environment, the framework addresses the limitations of existing approaches, offering a more comprehensive and ecologically valid perspective on psychopathology. In addition, the article proposes directions for future research, underscoring the significance of pluralism in the explanation of mental disorders and exploring the possibility of integrating extended cognition into the existing framework. These theoretical developments enhance multifaceted understandings of mental disorders, refine classification and explanatory methodologies, and inform the development of evidence-based, targeted treatment strategies. Collectively, these insights aim to advance the field of psychopathology toward a more integrated, inclusive, and practice-oriented realm, providing a robust theoretical foundation for innovative clinical approaches to mental health.